Determinants of left atrial reservoir and pump strain and use of atrial strain for evaluation of left ventricular filling pressure. (26th January 2021) - Inoue, Katsuji; Khan, Faraz H; Remme, Espen W; Ohte, Nobuyuki; García-Izquierdo, Eusebio; Chetrit, Michael; Moñivas-Palomero, Vanessa; Mingo-Santos, Susana; Andersen, Øyvind S; Gude, Einar; Andreassen, Arne K; Wang, Tom Kai Ming; et al.
Abstract: Aims: The aim of this study is to investigate determinants of left atrial (LA) reservoir and pump strain and if these parameters may serve as non-invasive markers of left ventricular (LV) filling pressure. Methods and results: In a multicentre study of 322 patients with cardiovascular disease of different aetiologies, LA strain and other echocardiographic parameters were compared with invasively measured LV filling pressure. The strongest determinants of LA reservoir and pump strain were LV global longitudinal strain (GLS) ( r -values 0.64 and 0.51, respectively) and LV filling pressure ( r -values −0.52 and −0.57, respectively). Left atrial volume was another independent, but weaker determinant of both LA strains. For both LA strains, association with LV filling pressure was strongest in patients with reduced LV ejection fraction. Left atrial reservoir strain <18% and LA pump strain <8% predicted elevated LV filling pressure better ( P < 0.05) than LA volume and conventional Doppler parameters. Accuracy to identify elevated LV filling pressure was 75% for LA reservoir strain alone and 72% for pump strain alone. When combined with conventional parameters, accuracy was 82% for both LA strains. In patients with normal LV systolic function by GLS, LA pump strain >14% identified normal LV filling pressure with 92% accuracy. Conclusion: Left atrial reservoir and pump strain are determined predominantly by LV GLS and filling pressure. Accuracy of LA strains to identify elevated LV filling pressure was best in patients with reduced LV systolic function. High values of LA pump strain, however, identified normal LV filling pressure with good accuracy in patients with normal systolic function. Graphical Abstract: